An ambient assisted living system for Alzheimer’s patients - Abedin, Minhajul; Ahad, Mohammad Abdul; Hasan-Ul-Banna, A.B.M; Khan, Nibraz; Hossain, Ashfaq (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.